Rimbaud’s influence on Jayne Anne Phillips: from Sweethearts to Shelter - Stéphanie Durrans (Transatlantica)
Arthur Rimbaud emerges from Jayne Anne Phillips’s essays as a continual source of fascination. This paper explores the patterns of convergence that unite these two writers one century apart while aiming to provide a deeper and more meaningful appreciation of Phillips’ accomplishments in Shelter. It focuses on Rimbaud’s and Phillips’ conception of language and their emphasis on "visionary writing", before investigating the significance of such patterns on Shelter and exploring the stylistic affinities linking their respective works. In the end, linguistic deconstruction and regeneration appears as one of the ways in which both writers seek to express the hidden traumas of a society in the grips of violence.